The impact of public sector scorecard adoption on the effectiveness of accounting information systems towards the sustainable performance in public sector - Pham Quang Huy; Vu Kien Phuc (Cogent Business & Management, 2020)
The effectiveness of accounting information system (AIS) in public sector organization (PSO) is well recognized to play an important part in obtaining sustainable performance (SP). Nevertheless, the effectiveness of AIS cannot achieve the SP on its own due to the rapid changing in the global economic world. Accordingly, there is an increasing demand on a framework of evaluation which is considered to be appropriate with the characteristics of PSO to orientate, manage, and assess operations of AIS toward attaining SP. Thus, this study is undertaken with the aim at exploring the relationship between the impact of public sector scorecard (PSS) implementations and effectiveness of AIS toward SP enhancement with evidence gathered from 883 PSOs' accountants in Mekong Delta region. Data analyzed by the Structural Equation Modeling (SEM) highlight that PSS adoption has a significant impact on the effectiveness of AIS. It also provides a reliable basis for the association between the effectiveness of AIS and SP. Although the topic of research is still immature, these findings are predicted to serve as a catalyst for scholars, practitioners, and policymakers to inquire and adopt because of its potential benefits in PSOs' operations.
Keywords: 650; accounting information system; public sector scorecard; public sector organization; sustainable performance